A rare case of spontaneous necrosis of primary renal cell carcinoma - Matsuzaki, Kyosuke; Imamura, Ryoichi; Iwanishi, Toshichika; Nakagawa, Masahiro; Tanigawa, Go; Tsutahara, Koichi; Shimazu, Kohki; Fushimi, Hiroaki; Tsuzuki, Toyonori; Yamaguchi, Seiji (Canadian Urological Association Journal, 2015)
A 42-year-old woman was referred to our hospital with a chief complaint of asymptomatic gross hematuria. Computed tomography revealed a 4-cm tumour in the left kidney and radical nephrectomy was performed. Microscopically, the tumour was completely necrotic and consisted of nests of cells with abundant cytoplasm and large nuclei. Immunohistochemical analysis indicated complete infarction of the chromophobe renal cell carcinoma. Two years after surgery, the patient remained recurrence-free.